2014
DOI: 10.1016/j.preteyeres.2014.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Stem cells as source for retinal pigment epithelium transplantation

Abstract: Inherited maculopathies, age related macular degeneration and some forms of retinitis pigmentosa are associated with impaired function or loss of the retinal pigment epithelium (RPE). Among potential treatments, transplantation approaches are particularly promising. The arrangement of RPE cells in a well-defined tissue layer makes the RPE amenable to cell or tissue sheet transplantation. Different cell sources have been suggested for RPE transplantation but the development of a clinical protocol faces several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 153 publications
(159 reference statements)
1
31
0
1
Order By: Relevance
“…The intercellular connections in 3D-RPE cells had important functions in the formation of the blood-retinal barrier, cell polarity, and intracellular communication [2]. Although SD-RPE cells also formed some characteristic ultrastructure of native RPE cells, we did not detect bipolar location of caveolaes and intercellular structures such as adherences junction and desmosomes.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…The intercellular connections in 3D-RPE cells had important functions in the formation of the blood-retinal barrier, cell polarity, and intracellular communication [2]. Although SD-RPE cells also formed some characteristic ultrastructure of native RPE cells, we did not detect bipolar location of caveolaes and intercellular structures such as adherences junction and desmosomes.…”
Section: Discussionmentioning
confidence: 63%
“…RPE can secrete nutrition factors, phagocytose photoreceptor outer segment (POS) and is involved in the formation of the blood-retinal barrier; the pigment granules in RPE cells have light-absorbing and anti-oxidative stress functions [1]. Dysfunction of RPE usually results in secondary degeneration of photoreceptor cells, thus causing sight-threaten diseases, including age-related macular degeneration (AMD) and Stargardt's macular dystrophy [2]. Unfortunately, no effective treatment is found for curing these retinal degeneration diseases currently.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…AMD, a progressive neurodegenerative condition primarily affects the retinal pigmented epithelium (RPE), secondarily resulting in degeneration of photoreceptors in people ≥ 50 years [2].…”
Section: Introductionmentioning
confidence: 99%
“…Stem cells withability to self-renew and differentiate into any cell type has been the promising source for AMD treatment. Stem cells that have been explored in animal models for the treatment of AMD include embryonic stem cells (ESCs) and human induced pluripotent stem cells (iPSCs) and mesenchymal stem cells (MSCs) [2,6]. In our previous studies we have shown the improvement in the patient's condition suffering from cerebral palsy, cortical visual impairment (CVI), Lyme's disease, spinocerebellar ataxia, Friedreich's ataxia and spinal cord injury after human embryonic stem cells (hESCs) therapy [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%